Morphine and Naloxone Facilitate Neural Stem Cells Proliferation via a TET1-Dependent and Receptor-Independent Pathway - Liang, Lining; Chen, Jinlong; Li, Yuan; Lai, Xiaowei; Sun, Hao; Li, Changpeng; Zhang, Mengdan; Yang, Tingting; Meng, Fei; Law, Ping-Yee; Loh, Horace H.; Zheng, Hui (Cell reports (Cambridge), 2020)
Normally, opioids function in a receptor-dependent manner. They bind to opioid receptors, activate or inhibit receptor activation, and subsequently modulate downstream signal transduction. However, the complex functions of opioids and the low expression of opioid receptors and their endogenous peptide agonists in neural stem cells (NSCs) suggest that some opioids may also modulate NSCs via a receptor-independent pathway. In the current study, two opioids, morphine and naloxone, are demonstrated to facilitate NSC proliferation via a receptor-independent and ten-eleven translocation methylcytosine dioxygenase 1 (TET1)-dependent pathway. Morphine and naloxone penetrate cell membrane, bind to TET1 protein via three key residues (1,880–1,882), and subsequently result in facilitated proliferation of NSCs. In addition, the two opioids also inhibit the DNA demethylation ability of TET1. In summary, the current results connect opioids and DNA demethylation directly at least in NSCs and extend our understanding on both opioids and NSCs. [Display omitted] •Naloxone and morphine facilitate NSC proliferation in a receptor-independent manner•Naloxone and morphine facilitate NSC proliferation in a Tet1-dependent manner•Naloxone and morphine bind TET1•Naloxone and morphine decrease the DNA demethylation activity of TET1 Liang et al. demonstrate a receptor-independent and Tet1-dependent pathway used by opioids naloxone and morphine to facilitate the proliferation of NSCs. The binding of naloxone and morphine to TET1 suggests that DNA methylation should be considered when studying the tolerance- and addiction-induced opioids.